Ordinances of the City of Norfolk, with the Amended Charter and an Appendix, at 115-16, ch. 33, § 1 (1894). - (:unkn) unknown (My University, 1894)
No person shall keep, in any house or store, any quantity of gunpowder exceeding two kegs or vessels thereof, of the weight of twenty-five pounds each,
Keywords: GUNPOWDER - STORAGE